Analysis of Student Concept Mastery Using the Project Based Learning Model Seen from Parents' Work - Misbah; Adha, Alfajri; Segalerba, Gianluigi; Nova Kafrita (Yayasan Nurul Yakin Bunga Tanjung, 2024)
The research that has been carried out aims to determine the influence of parents' work on students' mastery of concepts after being given the Project Based Learning (PjBL) learning model. The research method used was quantitative descriptive with the research population being all students of class XII MIPA at SMA 13 Bungo with a sample of 33 people selected using purposive sampling techniques. Data collection was carried out using an essay test, where the average student test score was 72.61 with the lowest score being 44 and the highest being 92 indicating a normal distribution. The t test was carried out on students' daily test scores, with tcount of -1.357 and ttable of 1.693 at a significance level of 0.05. tcount < ttable (-1.357 < 1.693), so the test hypothesis Ho is accepted, and Ha is rejected. The research results show that there is no significant influence of the PjBL model on student learning outcomes in parental work, especially in Dynamic Electricity material.